Perancangan Client Server Three Tier Pada Pembangunan Web Service Anggota Perpustakaan Universitas Muhammadiyah Bengkulu - Cahyo Prihantoro; Harry Witriyono (JTIS: Journal of Technopreneurship and Information System, 2019)
The design of the three-tier client server architecture is a further development than before that uses two tiers. The planning is the initial stage before the implementation of the system that is already running today. With this model it is expected that the application no longer need to be installed on every client but enough on the server only.Â  Beside that, this model of server side application can be accessed by every client in various operating system infrastructure and hardware. The Library transaction service workload can be dispersed and no longer overlap at one work terminal only, but it can already be spread over other terminals, which is the benefit of this technology.Â  The integrated information system between the academic information system and library information system makes the data more accurate and well distributed. The credibility and flexibility of data is maintained due to the synchronization between servers for data usage on the main server. This kind of model system development pattern makes integration between parts of an organization better. Three tiers have a database layer on server 1, the application layer on server 2, and Layer 3 is on the user side.